Intermediate Effects of Body Mass Index and C-Reactive Protein on the Serum Cotinine- Leukocyte Telomere Length Association - Gao, Xiao; Kong, Yawei; Li, Shengxu; Dong, Shiqiu; Huang, Xinyu; Qi, Deyu; Zhang, Tao; Yan, Yinkun; Chen, Wei (Frontiers in Aging Neuroscience, 2022)
We aimed to examine the association between serum cotinine and leukocyte telomere length (LTL) and the intermediate effects of body mass index (BMI) and C-reactive protein (CRP) on modulating the association. This study included 4,047 adults from the 1999 to 2002 National Health and Nutrition Examination Survey. In the combined sample, after adjusting for age, race, sex, physical activity, and alcohol use, the total effect of serum cotinine on LTL was significant (standardized regression coefficient, β = −0.049, p = 0.001) without BMI and CRP included in the model. With inclusion of BMI but without CRP in the model, the direct effect of cotinine on LTL in its absolute value increased to β = −0.053 (p < 0.001), and the suppression effect of BMI was estimated at 8.8%. With inclusion of CRP but without BMI in the model, the direct effect of cotinine on LTL in its absolute value decreased to β = −0.040 (p = 0.008), and the mediation effect of CRP was estimated at 16.9%. With inclusion of both BMI and CRP in the model, BMI and CRP still had significant suppression and mediation effects, respectively, on the cotinine-LTL association. These findings suggest that weight and inflammation have different roles in the inverse association between serum cotinine and LTL.